2017
DOI: 10.1097/ta.0000000000001676
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal cavity lavage reduces the presence of mitochondrial damage associated molecular patterns in open abdomen patients

Abstract: Background Mitochondrial damage-associated molecular patterns (mtDAMPs), such as mitochondrial DNA and N-formylated peptides, are endogenous molecules released from tissue after traumatic injury. mtDAMPs are potent activators of the innate immune system. They have similarities with bacteria, which allow mtDAMPs to interact with the same pattern recognition receptors and mediate the development of Systemic Inflammatory Response Syndrome (SIRS). Current recommendations for management of an open abdomen include r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…It is also possible that a larger amount of irrigation negates the possible benefits of the intervention through a yet unknown mechanism. While there is experimental evidence of at least one benefit to the use of irrigation in trauma victims [39], our results strongly suggest an upper limit of 5L for the effluent. This has relevance for today's practice, since epidemiological evidence exist for the current use of Intraoperative Peritoneal Lavage for this indication in surgical practice [41][42][43][44][45][46][47][48][49][50].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…It is also possible that a larger amount of irrigation negates the possible benefits of the intervention through a yet unknown mechanism. While there is experimental evidence of at least one benefit to the use of irrigation in trauma victims [39], our results strongly suggest an upper limit of 5L for the effluent. This has relevance for today's practice, since epidemiological evidence exist for the current use of Intraoperative Peritoneal Lavage for this indication in surgical practice [41][42][43][44][45][46][47][48][49][50].…”
Section: Discussionmentioning
confidence: 62%
“…During the last decade of the twentieth century (and in some more recent literature [25][26][27][28][29][30][31][32]) animal and other experimental studies began addressing the question of which fluid and how much [8,[25][26][27][33][34][35][36][37][38][39][40]. It was during this period that the potential adverse effects of the use of abdominal washouts were described: upregulation of pro-inflammatory mediators, damage to peritoneal mesothelial cells and polymorphonuclear neutrophil membranes, promotion of postoperative adhesions, documented instances of bacterial translocation, failure to effectively decrease peritoneal bacterial counts, and potential adverse effects on final hemostasis (through technical or chemical issues) [7,33].…”
Section: Discussionmentioning
confidence: 99%
“…They have also observed that contraction of the trachea and bronchi caused by NFPs is concentration-dependent. Martinez-Quinones et al hypothesized that increased frequency of peritoneal cavity lavage may reduce the risk of SIRS via decreasing the levels of mtDAMPs according to their pilot study [21]. Based on Martinez's finding, we suggest that more studies are needed to determine the role of extracellular NFPs in SIRS and their possible clinical applications.…”
Section: N-formyl Peptides (Nfps)mentioning
confidence: 78%
“…The elimination of mtDNA may be an effective means to improve the immune function of patients with sepsis. Martinez-Quinones et al [21] observed in the pilot study that abdominal cavity irrigation could reduce the concentration of ND6 (a kind of mtDAMPs) in peritoneal fluid of open abdomen patients. However, peritoneal lavage does not reduce the level of mtDNA in the abdominal cavity.…”
Section: Mtdnamentioning
confidence: 99%
“…This hypothesis of extracellular accumulation of cf-mtDNA prior to its detection in circulation is also supported by the observation of Martinez-Quinones et al in patients who underwent open abdominal surgery. Peritoneal lavage was associated with lower plasma mtDNA concentrations [ 33 ]. This demonstrates surgical reduction of extracellular mtDNA load prior to its entry into circulation and raises the possibility of timely mtDNA removal as a potential therapy.…”
Section: Release Of Cf-mtdna Via Cell Necrosis In Trauma and Surgerymentioning
confidence: 99%